The Urgency of Standardization of Transaction Policies in The Islamic Financial System in The Digital Era - Zulhilmi, Muhammad; Husna, Aulia (Manunggal Halim Jaya, 2025)
The development of information technology has revolutionized the financial industry, including the Islamic financial system. This study uses a descriptive-qualitative method with a literature review approach to explore the urgency of standardizing transaction policies in digital Islamic finance. The results show that the lack of comprehensive regulations and differing interpretations of Sharia contracts between institutions create legal uncertainty and potential doubts. Standardizing transaction policies is crucial to ensure compliance with Sharia principles and prevent practices that harm consumers. Furthermore, collaboration between regulators, fatwa authorities, and industry players is needed to develop specific regulations governing digital Sharia transactions. In conclusion, developing operational standards and improving public literacy are also crucial for creating an inclusive and sustainable Islamic financial ecosystem.